Generalized Invexity and Duality in Multiple Objective Variational Problems - Mukherjee R.N.; Mishra S.K. (My University, 2025)
Multiple objective programming problems with the concept of weak minima are extended to multiple objective variational problems. A number of weak, strong, and converse duality theorems are given under a variety of generalized invexity conditions. © 1995 Academic Press, Inc.